One Parent Type Family and Social Welfare: A Case Study of Nyarusiza Sub-County Kisoro District. - Duhimbaze, Emmanuel (Kabale University, 2023)
The study research report focused on the findings of the one-parent type family and social welfare in Nyarusiza sub county Kisoro district. The objectives of the study were to find out services provided by one parent type family to improve social welfare, to identify challenges faced by one parent type family towards improving social welfare, to suggest possible solutions to the challenges faced by one parent type family towards improving social welfare and to find out the relationship between one parent type family and social welfare. In chapter two, there was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on one-parent type family as an independent variable and social welfare as the dependent variable. In chapter three this is where the methods of data collection were put into action. The researcher used both qualitative and quantitative methods of data collection and analysis. The researcher used simple random sampling techniques in collecting and analyzing data and was used to provide equal chances to the sample size. Purposive sampling was also used to collect data from 80 respondents who participated in the study. The findings of the study obtained from the field interpreting revealed that most of the single-parent type families were of female respondents 56% and had attained a primary level of education, the findings further revealed that single-parent type families had a significant relationship with education services of the children and this was represented by 22% of the respondents who strongly agreed. The study recommended that society should take steps to help in overcoming the problems of one-parent type family whether is the single parent or the children. We should keep in mind that we want to live in a peaceful life and to look forward to a progressive society despite the nature of the family.